Sistem Informasi Pendataan Barang Masuk dan Keluar - Valendito Mangasih Hutauruk; Aufa Akmal; Fahmi Rama Anggara; Emi Sita Eriana (CV. Multi Kreasi Media, 2026)
Recording incoming and outgoing goods plays a crucial role in inventory management, but manual systems often lead to recording errors, messy data, and delays in preparing stock reports. Therefore, an information system is needed to improve the effectiveness and efficiency of inventory data management. This study aims to design an information system for recording incoming and outgoing goods to facilitate the recording, management, and presentation of inventory information, using descriptive methods through observation, interviews, and literature review.